Grammar I found a dollar walking home - solving common sentence problems - The Center for Humanities; Communications Park Video (Firm). (Mt. Kisco, N.Y. : The Center)
Identifies and helps remedy run-on sentences, comma splices, sentence fragments, disagreement of subject and verb, and other common sentence problems.
Title from title screen.
DVD format.
Keywords: English language -- Grammar -- 1950-; English language -- Sentences